Regional delamination strength in the human aorta underlies the anatomical localization of the dissection channel - Sokolis, Dimitrios P.; Papadodima, Stavroula A. (Journal of biomechanics, 2022)
Aortic dissection is a life-threatening event, during which a primary tear propagates along the aorta causing catastrophic delamination of the inner (intima with most of the media) from the outer layers (leftover media with adventitia). Our understanding of mode-I fracture resistance at different aortic regions is incomplete, although the anatomical localization of the dissection channel may be assigned to this factor. To determine whether the susceptibility to dissection propagation varied with aortic region, the average and standard deviation of peel tension (indices of adhesive strength between layers when pulled apart and its fluctuation) were measured in 24 cadaveric subjects. Measurements were made in the inner and outer quadrants of 9 consecutive regions. Strong regional heterogeneity was established that was age-related based on the following evidence: (1) the average and standard deviation of peel tension peaked in the ascending aorta, decreasing to almost constant values in the descending thoracic aorta, but increasing across the abdominal aorta; (2) axial differences were more pronounced in the inner quadrant, with differences among quadrants reaching significance proximally; (3) the average peel tension was greatly impaired from <40 to 40–60 but much less to >60-year-old subjects at most regions/quadrants, leading to non-uniform axial variations in all age groups; (4) gender affected little the data. This comprehensive series of delamination tests explains the clinical observation of most dissections initiating in the ascending aorta to extend distally and of few dissections initiating in the descending thoracic aorta to extend proximally, while supporting the increased vulnerability in aged subjects.